Solvability of BVPs for impulsive fractional differential equations involving the Riemann-Liouvile fractional derivatives - LIU, Yuji (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In this paper, we study two classes of BVPs for impulsive fractional differential equations. Some existence results for these boundary value problems are established. Some comments on three published papers are made. Mathematics Subject Classification (2010): 34K37, 34K45, 34B37, 34B15, 34B10, 92D25, 34A37, 34K15.